PENGARUH HARGA, KUALITAS PRODUK DAN GAYA HIDUP SEHAT TERHADAP KEPUTUSAN PEMBELIAN PADA PRODUK BEAR BRAND DI KEBUMEN - Diah Ayu Dwi Afidah; Indah Rohyani (Jurnal Inovasi Penelitian, 2023)
This study aims to determine the effect of price, product quality and a healthy lifestyle on purchasing decisions of bear brand products in kebumen. the method used is a quantitative method. the sample data taken in this study are people who buy and consume bear brands in kebumen regency, totaling 100 people as respondents. instruments or data collection tools in this study using a questionnaire / questionnaire. the analytical tool in this study is using multiple linear regression analysis. data analysis techniques used in this study include qualitative analysis and quantitative analysis consisting of validity test, reliability test, t test, f test, multiple linear regression test (likert scale). data were analyzed using spss 25 for windows. the results prove the first hypothesis that price partially has no influence on purchasing decisions. the results of the second hypothesis prove that product quality has a significant effect on purchasing decisions. the results of the third hypothesis prove that a healthy lifestyle has a significant effect on purchasing decisions. the results of the fourth hypothesis prove that price, product quality and a healthy lifestyle simultaneously or together have a significant effect on purchasing decisions